2024
DOI: 10.1037/tra0001295
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic symptomatology, meaning in life, and perceived family functioning in nonclinical trauma-exposed university students.

Abstract: Objective: This study aims to explore and analyze the associations among posttraumatic symptoms, meaning in life dimensions, and perceived family functioning in trauma-exposed university students. Method: Participants (N = 158) answered a sociodemographic questionnaire, the Posttraumatic Stress Global Assessment (Crespo et al., 2017), the Purpose in Life Test (Crumbaugh & Maholick, 1969), and the Family APGAR (Smilkstein, 1978). Results: Outcomes indicated several negative associations between posttraumatic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Second, through direct correlational analysis, 16 studies listed in Table 2 reported significantly reduced PTSD symptom levels among individuals with higher perceived MIL (Aiena et al., 2016; Arredondo & Caparrós, 2021, 2024; Ben‐Ezra et al., 2013; Bryan et al., 2020; Daneshvar et al., 2022; Davies et al., 2023; Feder et al., 2013, 2016; Fischer et al., 2020; Herr & Buchanan, 2020; Mehnert et al., 2012; Morse et al., 2023; Owens et al., 2009; Pietrzak & Cook, 2013; Quiroga‐Garza et al., 2021; Schulenberg et al., 2016). Contrary to the previous studies, which explored the mediation role of MIL, participants in these studies were almost exclusively from Western countries, with 14 studies conducted with samples of U.S. military veterans and two studies conducted in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Second, through direct correlational analysis, 16 studies listed in Table 2 reported significantly reduced PTSD symptom levels among individuals with higher perceived MIL (Aiena et al., 2016; Arredondo & Caparrós, 2021, 2024; Ben‐Ezra et al., 2013; Bryan et al., 2020; Daneshvar et al., 2022; Davies et al., 2023; Feder et al., 2013, 2016; Fischer et al., 2020; Herr & Buchanan, 2020; Mehnert et al., 2012; Morse et al., 2023; Owens et al., 2009; Pietrzak & Cook, 2013; Quiroga‐Garza et al., 2021; Schulenberg et al., 2016). Contrary to the previous studies, which explored the mediation role of MIL, participants in these studies were almost exclusively from Western countries, with 14 studies conducted with samples of U.S. military veterans and two studies conducted in Spain.…”
Section: Resultsmentioning
confidence: 99%